1000 new designs 2 and where to find them - Hudson, Jennifer (Laurence King Publishing, 2010)
Presents a roundup of the best in contemporary design, from around the world. This title includes chapters: Tables and chairs; Sofas and beds; Storage; Kitchens and bathrooms; Tableware; Textiles; Lighting; and, Electronics. It also includes commentaries that give insight into various developments in design and studies on selected products